EFFECTS OF PREOPERATIVE DULOXETINE ON SHORT-TERM OUTCOMES AFTER LAPAROSCOPIC SURGERIES: A SYSTEMATIC REVIEW AND META-ANALYSIS (CIPEEX, 2025)
Objective: To conduct a systematic review and meta-analysis to investigate the effects of preoperative duloxetine on short-term outcomes after laparoscopic surgeries. Methods: MEDLINE, Embase, and the Cochrane Library were systematically searched for randomized controlled trials comparing preoperative duloxetine vs. placebo in adults undergoing laparoscopic surgery. Risk ratios (RRs) and mean differences (MDs) with 95% confidence intervals (CIs) were used for dichotomous and continuous outcomes, respectively, using a random-effects model. Statistical significance was considered at p
Keywords: Postoperative; duloxetine; laparoscopic surgery; adult